Pengaruh Disiplin Kerja dan Kompensasi terhadap Kinerja Karyawan pada Klinik Tiara Cibinong Kabupaten Bogor - Camelia Putri; Eigis Yani Pramularso; Hardani Hardani (MAMEN: Jurnal Manajemen, 2025)
Tiara Clinic in Cibinong, Bogor Regency, is a health service institution that requires good employee performance in order to increase its contribution to the community. To achieve this employee performance, efforts must be made by paying attention to related aspects such as work discipline and employee compensation. This study aims to determine the effect of work discipline and compensation on employee performance at Tiara Clinic Cibinong, Bogor Regency. The study uses a quantitative method with data obtained through questionnaires. The study population includes all 33 employees, with a saturated sampling technique used. The analysis tool used was multiple regression, preceded by a classical assumption test with data processing using SPSS. The results of the study show that work discipline has a positive and significant effect on employee performance, and employee performance is also positively and significantly influenced by compensation. In addition, both of these factors together also have a positive and significant effect on improving employee performance at the Tiara Cibinong Clinic in Bogor Regency.